Modern possibilities of upper extremity regional anesthesia - Khmyzov, Andrij; Voloshyn, Mykyta (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Today, regional anesthesia is widely used during surgical interventions in orthopedic surgery. Blockades of individual nerves and plexuses are used. Objective. To introduce readers: surgeons, orthopedists-traumatologists with the possibilities of regional anesthesia like an adequate method of analgesia during upper limb interventions. Methods. Relevant literature from PubMed, Scopus, Google Scholar databases and own experience of regional anesthesia were analyzed. The results. The work describes the effect of regional anesthesia on the nervous, respiratory, cardiovascular and coagulation systems. Information about blocks of peripheral nerves of the upper extremities: interscalene, supraclavicular, subclavian, axillary. Their advantages and disadvantages were analyzed. Interscalene block is not recommended for patients with severe lung disease due to the risk of respiratory failure. Complications of this analgesia include: phrenic nerve block (up to 100 %), sympathetic chain block and Horner's syndrome. Also, possible accidental injection into the vertebral artery. Indications for the supraclavicular block are operations on the hand, forearm, elbow and shoulder. Complications — phrenic nerve block (17‒50 %), recurrent laryngeal blockade (22 %), pneumothorax (0.6‒6.1 %). When planning anesthesia, the accompanying pathology of the patient and his general condition should be taken into account. Particular care is required when the patient is taking anticoagulants. Risk of bleeding and thrombosis should be carefully assessed. Special attention should be paid to the toxicity of local anesthetics and ways to eliminate it. Conclusions. Regional anesthesia can be used in the pre-, intra- and postoperative periods. Sometimes it’s the only method that permit surgical intervention. It is necessary to understand all the advantages and limitations to ensure high quality of patient care.